Child Rights in India Challenges and Social Action - Chopra, Geeta; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2015)
The book is a comprehensive compendium on child rights in India from a child development perspective. It discusses the challenges that Indian children face for survival, development, and education, especially if they are marginalized through disability, lack of care, and poverty. The major issues expounded by the author in relation to rights are infant and child survival, early child development, street and working children, children in conflict with law, children with disabilities, child trafficking, and child sexual abuse. The author goes further to delve into the causes, among which are high population, poverty, migration, illiteracy, poor legislation and deep-rooted social norms and behaviour. The book presents the existing policy and legal framework in India for each of these issues. The broad purpose of the book is to comprehensively discuss the roadblocks that the marginalized child in India faces, to understand the causes of these roadblocks, and to evaluate government and civil society action for children in India.
Chapter 1. Introduction to Child Rights -- Chapter 2. The Situation of the Child in India: Quest for Equity -- Chapter 3. Early Childhood Care and Education: Right to Survival and Development -- Chapter 4. Children in Especially Difficult Circumstances: Right to Protection and Participation -- Chapter 5. The Working and the Street Children: Where is the Child? -- Chapter 6. Children in Conflict with Law: The Child Offender -- Chapter 7. Child Abuse in India: The Battered Child -- Chapter 8. Child Trafficking: The Victimised Child -- Chapter 9. Children with Disabilities: The Invisible Child.
Keywords: Social sciences; Child development; Human rights; Childhood; Adolescence; Social groups; Child psychology; School psychology; Social Sciences; Childhood, Adolescence and Society; Human Rights; Childhood Education; Child and School Psychology; Electronic books